Development of the BODY-Q Chest Module Evaluating Outcomes following Chest Contouring Surgery. Issue 6 (December 2018) - Klassen, Anne F.; Kaur, Manraj; Poulsen, Lotte; Fielding, Craig; Geerards, Daan; van de Grift, Tim C.; Hoogbergen, Maarten; Juhl, Claus Bogh; Lorenzen, Mike Mikkelsen; McEvenue, Giancarlo; McLean, Hugh; Moliver, Clayton; et al.
Abstract : Background: Plastic surgery to improve chest appearance is becoming increasingly popular. The BODY-Q is a patient-reported outcome instrument designed for weight loss and/or body contouring. In this article, the authors describe the development of a new module for masculinizing chest contouring surgery. Methods: Qualitative methods were used to develop the BODY-Q Chest Module, which was subsequently field-tested in Canada, the United States, The Netherlands, and Denmark between June of 2016 and June of 2017. Participants were aged 16 years or older and seen for gynecomastia, weight loss, or transman chest surgery. Data were collected using either a Web-based application or paper questionnaire. Rasch measurement theory analysis was performed. Results: The sample included 739 participants (i.e., 174 gynecomastia, 224 weight loss, and 341 gender-affirming). Rasch measurement theory analysis refined a 10-item chest scale and a five-item nipple scale. All items had ordered thresholds and good item fit, and scales evidenced reliability [i.e., person separation index and Cronbach alpha values were 0.95 and 0.98 (chest scale) and 0.87 and 0.94 (nipple scale), respectively]. Scores for both scales correlated more strongly with similar (satisfaction with the body) versus dissimilar (psychological and social function) BODY-Q scales. The mean scores for the chest and nipple scales were significantly higher ( p < 0.001 on independent samples t tests) in participants who were postoperative compared with preoperative. Conclusion: This new BODY-Q Chest Module is a clinically meaningful and scientifically sound patient-reported outcome instrument that can be used to measure outcomes for masculinizing chest contouring surgery. Abstract : Supplemental Digital Content is available in the text.Evidence-Based Outcomes Article.